Role of low‐voltage/NH fuselinks rated voltage in distribution network losses. An evaluation based on the Hellenic low‐voltage distribution network. Issue 5 (1st May 2014) - Psomopoulos, Constantinos S.; Ioannidis, George Ch.; Karras, Yannis
Abstract : Protection of low‐voltage power lines is fuses' main application. In every distribution network, hundreds of thousands fuses are operating continuously. These components, because of their operating characteristics, present power losses widely known as 'power dissipation', which are increased as their rated voltage is increased. In this work, the potential reduction of power losses in the Hellenic low‐voltage distribution network by selecting fuses with voltage equal to the networks nominal (400 V), instead of 500 V or even 690 V, is examined. The presented analysis and results clearly show that the NH‐fuses' rated voltage should be equal to the networks nominal and not higher, which will result in reduced power losses and increased low‐voltage distribution network capacity, less thermal stress of the equipment, reduction of the primary energy needs and CO2 emissions. Furthermore, the proposed replacement leads to slightly less spare parts cost and could be implemented gradually during scheduled maintenance resulting zero implementation cost. Since Greece is not the only case of a country in which electrical distribution network operator applies the previous mentioned practice, it is rather obvious that the resultant conclusions could be very helpful for other countries which use similar regulation to reconsider and revise it.